Competition law of the United States - Langer, Howard (Alphen aan den Rijn, The Netherlands : Kluwer Law International, 2013)
Derived from the renowned multi-volume'International Encyclopaedia of Laws', this practical analysis of competition law and its interpretation in the United States covers every aspect of the subject - the various forms of restrictive agreements and abuse of dominance prohibited by law and the rules on merger control; tests of illegality; filing obligations; administrative investigation and enforcement procedures; civil remedies and criminal penalties; and raising challenges to administrative decisions. Lawyers who handle transnational commercial transactions will appreciate the explanation of fundamental differences in procedure from one legal system to another, as well as the international aspects of competition law. Throughout the book, the treatment emphasizes enforcement, with relevant cases analysed where appropriate.
'This book was originally published as a monograph in the international encyclopaedia of laws/competition law'.
Includes bibliographical refrences and index.
Keywords: Antitrust law -- United States; Antitrust law -- United States -- Interpretation and construction